Efficacy of fine needle aspiration cytology in diagnosing soft tissue tumors - Parajuli, S; Lakhey, M (Journal of Pathology of Nepal, 2012)
Background: Fine needle aspiration cytology has an established role in the diagnosis of various neoplastic and non-neoplastic lesions. Its accuracy when applied by experienced and well trained practitioners matches that of histopathology in providing an equivocal diagnosis; so it can also be used as a very useful alternative to excision biopsy in the diagnostic workup of soft tissue tumors. Materials and Methods: This retrospective study was done in the Department of Pathology, Kathmandu Medical College for a period of one year from January 2006 to December 2006. A total of 60 cases presented with soft tissue tumors, of which only 50 were biopsied and the correlation done. A detailed history, clinical findings, routine relevant laboratory investigations and radiological findings were carried. Results: Fine needle aspiration cytology revealed diagnostic materials in 47 cases and 3 cases were inconclusive for a definite diagnosis. 40 cases were diagnosed as benign lesions and 7 cases as malignant lesions. Out of the benign cases, the most common were lipomas which accounted for 52.5% of cases followed by benign mesenchymal tumor- 17.5%. Out of the malignant cases 71.42% were diagnosed as malignant mesenchymal tumor and 28.57% as malignant nerve sheath tumor. The overall diagnostic accuracy of fine needle aspiration cytology in soft tissue tumors in the present study was 86%. The sensitivity and specificity of diagnosing benign soft tissue tumors was 97.36% and 66.67% respectively and for malignant soft tissue tumors 66.67% and 97.36% respectively. Conclusion: Fine needle aspiration cytology can be effective and reliable diagnostic tool in the evaluation of soft tissue tumors. It is highly sensitive to detect benign soft tissue tumors and highly specific for malignant soft tissue tumors. Journal of Pathology of Nepal (2012) Vol. 2, 305-308 DOI: http://dx.doi.org/10.3126/jpn.v2i4.6884